Plicní mukormykóza vyvolaná Rhizopus microsporus - Lysková, P; Žáčková, P; Petečuková, V; Hubka, V; Vašáková, M; Matěj, R; Čermák, J; Kubátová, A; Kolařík, M; Kozák, T; Hricíková, I (Klinicka mikrobiologie a infekcni lekarstvi, 2013)
We report a case of mycotic pneumonia in a patient with acute myeloblastic leukemia. Rhizopus microsporus was identified as an agent of mucormycosis and proven by microscopy and culture. The determination of the isolate was supported by molecular methods. Combined treatment with surgery (right-sided pneumonectomy) and systemic amphotericin B and posaconazole antifungal therapy was chosen. In this case, amphotericin B Neo-Sensitabs tablets gave false "resistant" results on Mueller-Hinton agar when using the disk diffusion test. There was a good correlation between the Etest (16 h) and the Sensititre YeastOne microplate (24 h) for amphotericin B.
Keywords: amfotericin B; plicní mykózy; Amphotericin B; Antifungal Agents; lidé; Mucormycosis; mukormykóza; antifungální látky; Rhizopus; Leukemia, Myeloid, Acute; Lung Diseases, Fungal; akutní myeloidní leukemie; Humans